The effects of different light qualities on the growth and nutritional components of Pleurotus citrinopileatus - Chen, Xiaoli; Liu, Yihan; Guo, Wenzhong; Wei, Xiaoming; Wang, Mingfei; Zhang, Xin; Zheng, Wengang (Frontiers in Nutrition, 2025)
Light is one of the key factors affecting the flavor of edible fungi. Pleurotus citrinopileatus were planted in a growth chamber in order to investigate the effects of different LED lights on the growth and development. Five treatments were set up in the experiment, namely white light (CK, as control), pure green light (G), pure blue light (B), pure red light (R) and far-red light (Fr). The results showed that: (1) R or Fr treatment caused deformities in Pleurotus citrinopileatus, showing a soft stipe, thin pileus, and shallow color. Compared with the control, the stipe length of Pleurotus citrinopileatus significantly decreased by 12.52% under treatment B, while the stipe diameter, pileus diameter, and fruiting body weight significantly increased by 35.52%, 18.30%, and 23.66%, respectively (P < 0.05). The color of Pleurotus citrinopileatus was more plump under B treatment, among which the spectral color parameters C and Hue increased by 2.72% and 1.64%, respectively. (2) B increased the proportion of umami and sweet amino acids [(UAA+SAA)/TAA] while decreased that of bitter amino acids in total amino acids (BAA/TAA) in Pleurotus citrinopileatus relative to the control. In addition, except for B treatment, other treatments (G, R, Fr) significantly reduced the content of mushroom flavored amino acids (e.g., Asp and Glu). (3) B increased the odor activity value (OAV) of key aroma compounds in Pleurotus citrinopileatus compared with the other light qualities in this study, while R increased the OAV of 1-octen-3-ol and 1-octen-3-one. However, considering that mushrooms cannot grow normally under R treatment, this study recommended blue light as the main light quality for industrial production of Pleurotus citrinopileatus.